The Syntax of Time : The Phenomenology of Time in Greek Physics and Speculative Logic from Iamblichus to Anaximander - Manchester, Peter (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
The fourth century Neoplatonist Iamblichus, interpreting Plotinus on the topic of time, incorporates a 'diagram of time' that bears comparison to the figure of double continuity drawn by Husserl in his studies of time. Using that comparison as a bridge, this book seeks a phenomenological recovery of Greek thought about time. It argues that the feature of motion that the word 'time' designates in Greek differs from what most modern scholarship has assumed, that the very phenomenon of time has been misidentified for centuries. This leads to corrective readings of Plotinus, Aristotle, Parmenides, and Heraclitus, all looking back to the final phrase of the fragment of Anaximander, from which this volume takes its title: "according to the syntax of time.".